Case Study: Learning Material-based on Model-Eliciting Activities to Enhance Problem Solving Abilities and Self Confident - Berlian, M Ridho Ratu; Hapizah, Hapizah; Susanti, Ely (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
This development research aims to describe a valid and practical learning material-based on Model-Eliciting Activities (MEAs) and its effect on problem-solving abilities and self-confidence. The subjects of this research were 36 students grade 10th at MA Negeri 1 OKU Timur. The type of research used is design research with a development study type. The instrument used test, questionnaire, walkthrough, and interview. The data analysis used descriptive techniques. The validity of learning material-based on the model eliciting activities (MEAs) is demonstrated from the results of the assessment carried out by the validator at the expert reviews stage where researchers will receive suggestions and comments in terms of content, construct, and language as well as comments and suggestions at the one-to-one stage. Meanwhile, practicality can be seen from the results at the small group stage. Learning material-based on model eliciting activities (MEAs) model has a potential effect on students' problem-solving abilities and self-confidence as seen from the results of the analysis of students' answers at the field test stage. Based on the results of the analysis of problem solving ability test scores, 29 students (80.56%) were in the positive category, while 7 students (19.44%) were negative or had not reached the minimum criteria for completing the test results. And also seen from the results of the analysis of students' answers to the self-confidence questionnaire, which shows that 17% of students have very positive self-confidence, 58% of students have positive self-confidence, 25% of students have negative self-confidence